ANALISIS KINERJA KEUANGAN PT SAT NUSAPERSADA Tbk SEBELUM DAN SESUDAH AKUISISI - Lilik Setyowati; Oktavianti Oktavianti; Catur Fatchu Ukhriyawati (Universitas Riau Kepulauan, 2015)
This study aimed to analyze the differences in performance of the company before and after the acquisition of PT Sat Nusapersada Tbk on year 2006-2009. Performance of the company before and after the acquisition, measured using four financial ratios, ie, Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE), and Current Ratio (CR). Quantitative methods used in this study. This study took data from public companies, in the form of financial statements of PT. Sat Nusapersada Tbk, which make acquisitions. This study also aims to determine the change in the company's financial performance before and after the acquisition. Analyses were performed using independent sample t-test and paired samples. The results of this study indicate that the financial ratios of the four studies, NPM, ROA, ROE, and CR, the two years before and two years after the acquisition, did not show a significant difference compared before and after the acquisition, although reports net loss / income showed a loss after.